2021
DOI: 10.3920/cep190075
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the sport-specific and functional characteristics of back pain in horse riders

Abstract: Currently, no standardised screening tools nor established interventions are available to address the characteristics of back pain (BP) specifically in horse riders. Therefore, the aim of this case-control study is to explore sport-specific and functional characteristics of BP in horse riders. 16 professional and 16 amateur riders (25±7 years) participated in two questionnaires (a sport-specific questionnaire and the Oswestry Disability Index questionnaire) and were examined via the physical functional movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
2
5
0
Order By: Relevance
“…This value, considerably lower than those reported in previous studies [31], may reflect that half of the respondents stated that equestrianism was not their main occupation (non-professionals). A similar value was found in a case-control study on sport-specific and functional back pain features in horse riders, including 16 professional and 16 amateur riders [1]. A cross-sectional study in equestrian athletes reported a value of 74.2% for 12-months LBP [9].…”
Section: Prevalence Of Low Back Pain In the Past 12 Months And Associ...supporting
confidence: 77%
See 3 more Smart Citations
“…This value, considerably lower than those reported in previous studies [31], may reflect that half of the respondents stated that equestrianism was not their main occupation (non-professionals). A similar value was found in a case-control study on sport-specific and functional back pain features in horse riders, including 16 professional and 16 amateur riders [1]. A cross-sectional study in equestrian athletes reported a value of 74.2% for 12-months LBP [9].…”
Section: Prevalence Of Low Back Pain In the Past 12 Months And Associ...supporting
confidence: 77%
“…In this study, the 12-month prevalence of LBP was higher in female riders, even though sex, practicing other sports, or warming up before riding had no statistical significance in the occurrence of LBP. Previous studies have also found no connection between sex [1,9,32], practicing other physical activity [9], and LBP in equestrians, even though other authors [5,11] have established that participating in other sporting activities and physical fitness can help equestrian athletes to prevent spinal injury. Age, BMI, and years of equestrian practice were not significantly different between groups with and without LBP in the past 12 months.…”
Section: Prevalence Of Low Back Pain In the Past 12 Months And Associ...mentioning
confidence: 96%
See 2 more Smart Citations
“…Of the 60 articles, most were surveyed in athletes in Germany [14,18,49,[52][53][54][55][56][57][58][59][60][61][62], in Sweden [3,[63][64][65][66], and in Iran [36,37,[67][68][69]. Moreover, also in Norway [11,70,71], Poland [72][73][74], United States [50,51,75], the Netherlands [76,77], Belgium [78], Switzerland [12,79], Finland [80,81], Australia [82,83], Spain [84,85], Saudi Arabia [86,87], Estonia [88], Serbia [89], New Zealand [90], Ukraine [91], China…”
Section: Resultsmentioning
confidence: 99%